Polysaccharides from Artocarpus heterophyllus Lam. (jackfruit) pulp improves intestinal barrier functions of high fat diet-induced obese rats - Zeng, Shunjiang; Cao, Jun; Chen, Yuzi; Li, Chuan; Wu, Gang; Zhu, Kexue; Chen, Xiaoai; Xu, Fei; Liu, Qibing; Tan, Lehe (Frontiers in Nutrition, 2022)
Polysaccharides show protective effects on intestinal barrier function due to their effectiveness in mitigating oxidative damage, inflammation and probiotic effects. Little has been known about the effects of polysaccharides from Artocarpus heterophyllus Lam. pulp (jackfruit, JFP-Ps) on intestinal barrier function. This study aimed to investigate the effects of JFP-Ps on intestinal barrier function in high fat diet-induced obese rats. H&E staining and biochemical analysis were performed to measure the pathological and inflammatory state of the intestine as well as oxidative damage. Expression of the genes and proteins associated with intestinal health and inflammation were analyzed by RT-qPCR and western blots. Results showed that JFP-Ps promoted bowel movements and modified intestinal physiochemical environment by lowering fecal pH and increasing fecal water content. JFP-Ps also alleviated oxidative damage of the colon, relieved intestinal colonic inflammation, and regulated blood glucose transport in the small intestine. In addition, JFP-Ps modified intestinal physiological status through repairing intestinal mucosal damage and increasing the thickness of the mucus layer. Furthermore, JFP-Ps downregulated the inflammatory genes (TNF-α, IL-6) and up-regulated the free fatty acid receptors (GPR41 and GPR43) and tight junction protein (occludin). These results revealed that JFP-Ps showed a protective effect on intestinal function through enhancing the biological, mucosal, immune and mechanical barrier functions of the intestine, and activating SCFAs-GPR41/GPR43 related signaling pathways. JFP-Ps may be used as a promising phytochemical to improve human intestinal health.